2022
DOI: 10.1002/cptc.202200041
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State Proton Transfer Dynamics of a Super‐Photoacid in Acetone‐Water Mixtures

Abstract: Super‐photoacids, that is, photoacids with a negative pKnormala value in the electronically excited state, can trigger an excited‐state proton transfer (ESPT) to the solvent. For the neutral pyranine‐derived super‐photoacid studied here, even indications for ESPT in acetoneous solution are reported. The characteristics of ESPT in this environment, that is, which intermediates exist and what the impact of cosolvents is, remain unsettled though. In this work, we study ESPT in acetone‐water mixtures by steady‐st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Furthermore, the experimental results have shown that specific molecular interactions between the photoacid B and the solvent or other proton acceptors become relevant in acetone solution. 60 This motivated us to include explicit solvent molecules in the first solvation shell and to study their effect on the electronic excitation energies of this photoacid.…”
Section: Beyond Implicit Solvationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the experimental results have shown that specific molecular interactions between the photoacid B and the solvent or other proton acceptors become relevant in acetone solution. 60 This motivated us to include explicit solvent molecules in the first solvation shell and to study their effect on the electronic excitation energies of this photoacid.…”
Section: Beyond Implicit Solvationmentioning
confidence: 99%
“…55 As an aprotic and only moderately basic solvent, acetone is a quite unusual medium for PT reactions. Most recently, the ESPT of photoacid B has been studied experimentally in acetone–water mixtures 60 and neat acetone. 61 The study in acetone–water mixtures showed that a reaction complex between the photoacid and water—formed either already in the ground state or directly after excitation—becomes crucial for the ESPT dynamics of photoacid B in these solvent mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvatochromic properties as well as ESPT kinetics , have been studied experimentally in a variety of solvents including water, methanol, ethanol, and DMSO. Recently, the dynamics and ESPT intermediates of a strongly hydrogen-bonded complex of compound A with a trialkylphosphine oxide in nitrile solution were elucidated. , Furthermore, for the strongest superphotoacid B of that class, namely tris­(1,1,1,3,3,3-hexafluoropropan-2-yl)-8-hydroxypyrene-1,3,6-trisulfonate (p K a * ≈ −4 in water), the possibility of ESPT in acetone–water mixtures and in neat acetone were demonstrated . Despite the wealth of experimental knowledge regarding this photoacid, only limited information on the molecular origin of the exceptionally high photoacidity is yet available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, we followed closely the computational procedure described in References [24–26]. This is in particular of interest in light of recent studies of super photoacids in this solvent, 35,36 where previous implementations of COSMO excited‐state energy gradients for efficient wave function‐based methods 37,38 offer the possibility to employ these LFER parameters for COSMO in future applications on normalpKa*.…”
Section: Introductionmentioning
confidence: 99%